Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Minat Belajar Siswa Kelas X IPS 3 SMAN 6 Padang - Dara Cahya Purnama; Ike Sylvia (Naradidik: Journal of Education and Pedagogy, 2022)
This research is motivated by the low interest in learning of students in sociology at SMA N 6 Padang. The purpose of this study is to analyze the increase in students' interest in learning sociology in class X IPS 3 SMA N 6 Padang through the application of the make a match type of cooperative learning model. The method used in conducting this research is Classroom Action Research (CAR) with the aim of improving problems in the classroom. This study uses a design from Kemmis and McTaggart, namely the determination of the focus of the problem, action planning, observation/observation and data collection, and reflection. The sample in this study was 35 students of class X IPS 3 at SMA N 6 Padang. The data from this study were collected from observation sheets, questionnaires and interviews which were analyzed using quantitative analysis techniques taken from observation data and questionnaires while qualitative analysis techniques were from interview data. The theory used to analyze this research is the meaningful theory proposed by David Ausubel. During the second cycle, there were 4 meetings with social research material. The results showed that the percentage of observation of students' interest in learning in the first cycle was 40.17% while in the second cycle it was 87.13%. The results of the interest in learning questionnaire before taking the student's interest in learning were 30.09%, after the action the results of the interest in learning questionnaire were 91.57%. After the action, the results of the interview showed that after the learning was carried out by applying the make a match type of learning model students' interest in learning.